2016
DOI: 10.1159/000443021
|View full text |Cite
|
Sign up to set email alerts
|

High Fluoride Dentifrices for Elderly and Vulnerable Adults: Does It Work and if So, Then Why?

Abstract: The primary aim of this work is to present the available evidence that toothpastes containing >1,500 ppm fluoride (2,500-2,800 and 5,000 ppm F) provide an additional caries preventive effect on root caries lesions in elderly patients compared to traditional dentifrices (1,000-1,450 ppm F). The secondary aim of this paper is to discuss why high fluoride dentifrices in general should perform better than traditional F-containing toothpaste. When examining the few studies that have considered the preventive benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 32 publications
1
32
0
7
Order By: Relevance
“…Brushing with fluoride toothpaste at least twice a day is recommended. In individuals with high caries risk, root caries incidence, may decrease by changing a conventional toothpaste (1450 ppm fluoride) to a 5000 ppm fluoride toothpaste, when prescribed by a dentist [41][42][43] . For primary and secondary prevention of root caries lesions, a recent meta-analysis revealed that regular use of dentifrice containing 5000 ppm fluoride and quarterly professionally applied chlorhexidine or silver diamine fluoride varnishes may inactivate the existing and/or reduce the initiation of new root caries.…”
Section: Prevention Of Dental Caries and Periodontal Diseasementioning
confidence: 99%
“…Brushing with fluoride toothpaste at least twice a day is recommended. In individuals with high caries risk, root caries incidence, may decrease by changing a conventional toothpaste (1450 ppm fluoride) to a 5000 ppm fluoride toothpaste, when prescribed by a dentist [41][42][43] . For primary and secondary prevention of root caries lesions, a recent meta-analysis revealed that regular use of dentifrice containing 5000 ppm fluoride and quarterly professionally applied chlorhexidine or silver diamine fluoride varnishes may inactivate the existing and/or reduce the initiation of new root caries.…”
Section: Prevention Of Dental Caries and Periodontal Diseasementioning
confidence: 99%
“…28 This outcome was expected since it is already established that 5000 ppm F-dentifrice provides a better prevention and arrestment of carious root lesions. [29][30][31][32] Nevertheless, it has an important clinical relevance because with the population ageing in many countries, 33 root caries will be increasingly present in the routine of dental practices and the use of high-fluoride dentifrice could be an option to manage root caries in those particular patients. To the best of our knowledge, this is the first study that evaluates the role of high-fluoride dentifrice on root caries using different frequencies of sucrose exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The international evidence for adult use of 1.5 mg/g fluoride (or 1500 ppm) toothpaste is supportive of the benefits to adults and older persons, but care should be taken in the interpretation of the effectiveness and efficiency given the variability in populations and the scarcity of dedicated, longitudinal clinical trials specifically controlling for enumerable confounding factors. Evidence for the use of 5 mg/g fluoride (5000 ppm) toothpaste, specifically in populations at high risk is more compelling and could guide good practice in most situations specific to older dentitions at elevated risk to caries . Allied health practitioners, registered or enrolled nurses and Indigenous health workers who have been trained and are competent might be engaged in the provision of toothbrushing and toothpaste advice to individuals and groups of older Australians.…”
Section: The National Guidelines On Fluoride Use 2019mentioning
confidence: 99%
“…Evidence for the use of 5 mg/g fluoride (5000 ppm) toothpaste, specifically in populations at high risk is more compelling and could guide good practice in most situations specific to older dentitions at elevated risk to caries. 38,39 Allied health practitioners, registered or enrolled nurses and Indigenous health workers who have been trained and are competent might be engaged in the provision of toothbrushing and toothpaste advice to individuals and groups of older Australians.…”
Section: Toothpaste For Children and Adultsmentioning
confidence: 99%